Effects of the Covid-19 Pandemic on Islamic and Conventional Financial Markets - Saed Aljaed, Saiyer (International Journal of Scientific Research and Management (IJSRM), 2023)
The recent global Covid-19 pandemic is resentfully affecting global financial markets which including both Islamic and conventional stock markets. This study conducted an empirical examination to investigate the extent to which Covid-19 result on both Islamic and conventional financial markets, particularly the interconnections within the market activities. Data were collected from several national sources from 6 June 2020 to 27 September 2022, in two main periods. The study determined wavelet correlations among different variables to examine the effects of the pandemic. The findingsshow that the number of Covid-19 deaths was a significant determinant factor within the Islamic stock markets, contrary to conventional stock markets. Moreover, the results showed a positive link between the number of Covid-19 deaths and the Morgan Stanley capital International (MSCI) emerging market Asia Islamic index and the MSCI emerging Asia index. The link between exchange rates and crude oil in MSCI Gulf Corporation Council (GCC) countries combined was uncertain. However, this had a weak effect on Islamic indices and a strong effect on conventional indices. These findings contribute to assisting both investors and the market in optimising investment and market strategies.